Study factors associated with poor glycemic control in type 2 diabetes mellitus patients in tertiary care center - Mathuriya, Anita; Abbas , Shahid (International Journal of Research in Medical Sciences, 2023)
Background: Poor glycemic control is a major public health issue among patients with type 2 diabetes mellitus and a significant risk factor for the progression of diabetic complications. This study aimed to assess the magnitude and contributing factors of poor glycemic control among type 2 diabetes patients. Methods: A cross-sectional study was conducted among 150 type 2 diabetes patients a sample of 150 type 2 diabetics of both sexes was obtained diabetes in medicine OPD, any type 2 diabetes patient at the healthcare facilities over the age of 18 was eligible to participate in the study. Results: Of the 150 type 2 diabetes patients included in the study, 118 had poor glycemic control. Mean age was 59.67 (SD = 9.617) years; 115 (76.9%) of them were men. Most patients [n = 62 (41%)] used insulin or oral anti-diabetics as monotherapy [n = 32 (21%)] to regulate their blood sugar levels. The glycemic control got worse the longer the patient had diabetes, from 5 to 10 years (OR = 1.74) to more than 10 years (OR = 2.55), compared to patients with less than 5 years of illness. In comparison to patients with co-morbidity, patients without co-morbidity had significantly better glycemic control (OR=1.56). Conclusions: Gender, age, BMI, occupation, medical history, medication history, triglycerides, HDL, duration of diabetes, type and number of diabetes medications, and HbA1c were significantly associated. These factors can identify patients at risk of poor glycemic control, allowing targeted interventions for optimal outcomes. Adherence, physical activity, diabetes education, and training affect glycemic control, but this study did not.